Implementasi Kesehatan dan Keselamatan Kerja (K3) bagi Pekerja Lapangan di Pelabuhan New Priok Container Terminal 1 - Supartini Supartini; Vivid Dekanawati; Budi Handojo; Khoirudin Juniarto (Sekolah Tinggi Maritim Yogyakarta, 2021)
Occupational Health and Safety (K3) is a necessity for everyone in carrying out work and daily activities. Undisciplined worker behavior factors, inappropriate work methods, changes in workplaces, equipment, causes of work accidents. In order to ensure the implementation of K3, NPCT1 implements regulations that must be obeyed by all workers, employees and visiting guests. In this study, the authors used a qualitative research method with a descriptive approach. Occupational Health and Safety (K3) and security are carried out very strictly and consistently so that it runs according to the stipulations. K3 is carried out by HSSE staff directly, the number of personnel is 16 (sixteen), divided into 4 teams with excellent and professional performance in carrying out Port Patrol Inspection.NPCT1 has a Port Clinic as a health service for workers. Port Clinic is manned by 2 (two) doctors and 4 (four) paramedics. With careful preparation, very strict implementation and supervision and consistent evaluation in the implementation of K3, then within a period of 3 (three) consecutive years, from 18 August 2016 to 18 August 2019, there were no accidents (Zero Accident), so NPCT1 received appreciation of the Zero Accident Award in the form of a Zero Accident Award from the manager of Tanjung Priok Port.